Social disruptions & the 4th Industrial Revolution In Muslim World - Abdul Razak, Dzulkifli (2019)
ICRIIM is an International Class Joint Conference held in order to advance relation between University of Darussalam (UNIDA) Gontor and International Islamic University Malaysia (IIUM) which had been established since 2015 especially between Faculty of Ushuluddin UNIDA Gontor (Fakultas Ushuluddin UNIDA Gontor) and Department Usul al-Din and Comparative Religion Kulliyyah of Islamic Revealed Knowledge and Human Sciences (IRKHS) IIUM. As such, ICRIIM aims to reveal, identify, and find solutions to various religious issues in Indonesia and Malaysia. It is expected that scholars in both countries can be more sensitive in overcoming various issues of conservatism, radicalism, and violence in the name of religion and can also maintain harmony and coexistence in the two countries. Furthermore, this conference also intended to find out the real actions can be taken by higher education institution and religious observer in order to maintain religious diversity and coexistence in the region of South-East Asia especially in Indonesia and Malaysia through what we define as 'Samaahatu al-Islaam'.